Halal Trip Scheme: Implementation of Shariah Compliance in Indonesia - Riska Sayidah; Zahra Fitria; Sintia Nurul Fuadah; Rizal Faozi; Jaenudin Jaenudin; Agi Attaubah Hidayat (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: This study aims to analyze the implementation of the halal travel scheme in Indonesia and evaluate its compliance with sharia economic law, particularly focusing on standards set by DSN-MUI Fatwa No. 108/2016. Method: Using normative legal methods through a study of relevant legal regulations and literature, especially DSN-MUI Fatwa No. 108/2016. The study focuses on key sharia principles and assesses their application within the halal trip scheme, especially through innovations like the